Prototypicality and Acquisition of Chinese Resultative Verb Compounds among Learners of Chinese as a Foreign Language - Yafeng, Zhang (UNIMAS, 2024)
Chinese Resultative Verb Compound (RVC) is a frequently-used compound word in Chinese everyday speech and a crucial item prescribed in the curriculum and lexical syllabus of teaching Chinese to speakers of other languages (TCSOL). Nevertheless, there were enormous errors committed by Chinese as a second or foreign language (CSL/CFL) learners and evidence for prototypicality and its consistency in predicting SLA in prior studies. These errors and evidence posed challenges to the agreed-on frequency-based sequencing of RVC in the current lexical syllabus and the presentation of intuition-based illustrative examples in the classroom. Thus, this research was aimed to investigate the inter-dependency of LP, SeP and SyP of Chinese RVC through prototyping the RVC instruction. To this end, a three-phase exploratory mixed-method study was adopted to investigate the lexical prototypicality (LP) and syntactic prototypicality (SyP) of RVC and then to test those findings in quasi-experimental research. Phase I aimed to develop unitary definitions of RVC, including LP, semantic prototypicality (SeP) and SyP by reviewing the relevant literature. Subsequently, in Phase II, adopting a convergent design, prototype-based analyses of component morphemes of RVC and sentences licensed by RVC identified in Phase I were conducted, utilizing Gilquin and McMichael’s (2018) “convergence criterion of the prototype” framework. To test the effect of prototype-based RVC instruction translated from the findings in Phase II, a quasi-experiment design was adopted using pretest-post test control group design in Phase III. In the quasi-experiment study, 42 intermediate CFL learners were recruited from two intact classes in a middle school in Sibu, Sarawak. These learners took Chinese Proficiency Test (CPT), Lexical Acceptability Judgment Test (L-AJT) and Syntactic Acceptability Judgement Test (S-AJT) before and after the prototype-based RVC instruction, once for pretest and once for posttest (only L-AJT and S-AJT). Accordingly, independent sample t-test and multiple linear regression analysis were conducted for both L-AJT and S-AJT. Phase II results have demonstrated that, prototype-based graded membership of V1s, RCs and alternative sentences, as well as the prototype-based syntactic scale were produced. Additionally, in Phase III, the prototypicality of RC, token frequency of RVCs and prototype-based RVC instructions were found to significantly affect CFL learners’ performance in L-AJT, except for the insignificant effect of V1. In contrast, SeP (including the prototypicality of polysemous V1(打da3 “beat”) and semantic orientation of RC) and SyP had significant effects on learners’ performance in S-AJT, excluding the role of LP and prototype-based RVC instruction. The high residue of the models obtained from L-AJT and S-AJT indicates that further investigation was required. Based on the research findings, the prototype-based Dual Route Processing Modal and Tripartite Framework, as well as the prototype-based approach to vocabulary learning were put forward and suggested to predict the CFL learners’ compound identification of RVC and joint role of prototype-based instruction, LP, SeP and SyP in syntactic acceptability of RVC. It can be implicated that for intermediate CFL learners, RVCs should be introduced to the learners of Chinese as a foreign language in the CFL classroom based on the prototype-based sequencing of V1s and RCs: the most prototypical V1s and RCs should come first for beginner level CFL learners. In addition, prototypical syntactic patterns, such as SVO or Ba-C should be given to CSL/CFL learners to facilitate the RVC learning. Noticeably, the choice of prototypical sentence was a function of the semantic orientation of RC, SyP and the transitivity of LP.